IMF lending to developing countries : issues and evidence - Bird, Graham R. (London ; New York : Routledge, 1995)
Recent years have seen IMF lending focusing almost exclusively on the developing world as richer countries have turned to more flexible sources of finance. This provides the first analysis of Fund lending and key changes needed for future success.
Book Cover; Title; Contents; List of figures; List of tables; Preface; THE IMF AND DEVELOPING COUNTRIES; IMF LENDING: THE ANALYTICAL ISSUES; IMF LENDING: THE EMPIRICAL EVIDENCE; IMF LENDING: THE WAY FORWARD; Notes; References; Index.
Includes bibliographical references (pages 179-184) and index.
Print version record.
Keywords: International Monetary Fund; International Monetary Fund; Debts, External -- Developing countries; Loans, Foreign -- Developing countries; Debts, External; Loans, Foreign; Developing countries